What predicts esports betting? A study on consumption of video games, esports, gambling and demographic factors - Macey J; Abarbanel B; Hamari J (SAGE PUBLICATIONS LTD, 2022)
The parallel media related to sports, gaming and gambling are expanding, exemplified by the emergence of esports and game-related gambling (e.g. loot boxes, esports betting). The increasing convergence of these phenomena means it is essential to understand how they interact. Given the expanding consumer base of esports, it is important to know how individuals' backgrounds and consumption of game media may lead to esports betting. This study employs survey data (N = 1368) to investigate how demographics, alongside consumption of video games, esports and gambling can predict esports betting activity. Results reveal that both spectating esports and participation in general forms of gambling are associated with increased esports betting, no direct association was observed between the consumption of video games and esports betting. Findings suggest that while games may act as a vehicle for gambling content, highlighting the convergence of gaming and gambling, there is no intrinsic aspect which directly encourages gambling behaviours.